Sustainable Continuous Flow Valorization of γ‐Valerolactone with Trioxane to α‐Methylene‐γ‐Valerolactone over Basic Beta Zeolites. Issue 12 (6th June 2019) - Al‐Naji, Majd; Puértolas, Begoña; Kumru, Baris; Cruz, Daniel; Bäumel, Marius; Schmidt, Bernhard V. K. J.; Tarakina, Nadezda V.; Pérez‐Ramírez, Javier
Abstract: The need for more sustainable products and processes has led to the use of new methodologies with low carbon footprints. In this work, an efficient tandem process is demonstrated for the liquid‐phase catalytic upgrading of lignocellulosic biomass‐derived γ‐valerolactone (GVL) with trioxane (Tx) to α‐methylene‐γ‐valerolactone (MeGVL) in flow system using Cs‐loaded hierarchical beta zeolites. The introduction of mesopores along with the presence of basic sites of mild strength leads to MeGVL productivity 20 times higher than with the bulk beta zeolite, reaching 0.325 mmol min −1  gcat −1 for the best‐performing catalyst, the highest value reported so far. This catalyst proves stable upon reuse in consecutive cycles, which is ascribed to the partial depletion of the basic sites. The obtained MeGVL is subjected to visible‐light‐induced polymerization, resulting in a final material with similar properties to the widely used poly(methyl) methacrylate. Abstract : Sustainable tandem flow process : α‐Methylene‐γ‐valerolactone (MeGVL) is synthesized from lignocellulosic biomass‐derived γ‐valerolactone (GVL) in the presence of trioxane (Tx) using tailored Cs‐loaded hierarchical beta zeolite catalysts (see figure). The obtained MeGVL is subjected to a visible‐light‐induced polymerization reaction, giving a final material with similar properties to poly(methyl) methacrylate.